2014
DOI: 10.4149/av_2014_01_3
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells retrovirally transduced with prodrug-converting genes are suitable vehicles for cancer gene therapy

Abstract: Summary. -Mesenchymal stem/stromal cells (MSC) possess a set of several fairly unique properties which make them ideally suitable both for cellular therapies and regenerative medicine. These include: relative ease of isolation, the ability to differentiate along mesenchymal and non-mesenchymal lineages in vitro and the ability to be extensively expanded in culture without a loss of differentiative capacity. MSC are not only hypoimmunogenic, but they mediate immunosuppression upon transplantation, and possess p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 69 publications
(95 reference statements)
1
19
0
Order By: Relevance
“…1 Mesenchymal stromal cells (MSC) were proven to be suitable cellular vehicles for GDEPT approaches. [2][3][4] MSC represent a population with high proliferation capacity 5,6 and the genetic engineering does not compromise their key properties; therefore they can serve for the cell-directed enzyme/prodrug therapy (CDEPT) in the antitumor treatment. 7 Moreover, several studies demonstrated the inherent chemoresistant properties of the MSC that enable them to withstand the suicide effect and thus prolong the bystander toxicity exerted on the neighboring tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 Mesenchymal stromal cells (MSC) were proven to be suitable cellular vehicles for GDEPT approaches. [2][3][4] MSC represent a population with high proliferation capacity 5,6 and the genetic engineering does not compromise their key properties; therefore they can serve for the cell-directed enzyme/prodrug therapy (CDEPT) in the antitumor treatment. 7 Moreover, several studies demonstrated the inherent chemoresistant properties of the MSC that enable them to withstand the suicide effect and thus prolong the bystander toxicity exerted on the neighboring tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, MSCs have been studied as vehicles to deliver anti-cancer treatments because there is evidence that MSCs home to tumour sites. They can be induced to express anti-cancer proteins [e.g., interleukin (IL) 2], to produce pro-drug activating enzymes, which ensures that the active drug will only be localized in the tumour, or to deliver oncolytic viruses [20][21][22][23] . For these applications, the homing and persistence of MSCs in the target tissue are desirable [24] .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms operating in various GEPT are different and therefore the biological properties of given cell types are important to be evaluated. Most GEPT employs viral vector mediated gene transfer protocols, which are usually limited by the restricted ability of the virus to track cancer cells infiltrating into the surrounding tissue and its low migratory capacity towards the tumor, implying that combination of cellular therapy and gene delivery is an attractive option (72). For GESTECs expressing prodrug-converting genes, the response of tumor cells associated with gap-junctional intercellular communication (GJIC) and expression of enzymes involved in drug metabolism and ABC transporters should be taken into consideration for the selection of the most efficient treatment strategy (73).…”
Section: Resultsmentioning
confidence: 99%